(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Contemporary relevance as a category of the didactics of history teaching includes not only historical facts which might be deemed the causes of present-day problems and circumstances but also those which, on the grounds of the values or ideas inherent in them, are identical, equivalent, or contrary to present-day problems or notions. A context of meaning is created between present and past which gives rise to orientation knowledge, making it possible to reflect on solutions to present-day problems, to think of alternatives to habitual contemporary patterns of thinking and living, and to develop future perspectives. Selected examples of the various aspects of contemporary relevance are discussed, such as the conflict between Israelis and Arabs in the Middle East, and the role of religion at various times in history. The consequences arising from this category for both the didactic and subjectspecific training of History teachers will be discussed, as well as the nature of the relationship between subject-specific and didactic training.